Respostas

2014-09-01T18:22:26-03:00
Oi George.

2^{ 2x+2 }-6^{ x }-2*3^{ 2x+2 }=0\\ 2^{ 2x }*4-(2^{ x }*3^{ x })-2*3^{ 2x }*9=0\\ 4*2^{ 2x }-2^{ x }*3^{ x }-18*3^{ 2x }=0

Multiplica todo mundo por:

(\frac { 1 }{ 2^{ x }*3^{ x } } )

4*\frac { 2^{ x } }{ 3^{ x } } -1-18*\frac { 3^{ x } }{ 2^{ x } } =0

Fazendo a mudança de variável.

\frac { 2^{ x } }{ 3^{ x } } =y

4y-1-\frac { 18 }{ y } =0\\ 4y^{ 2 }-y-18=0\\ \\ \Delta =b^{ 2 }-4ac\\ \Delta =(1)^{ 2 }-4*4*(-18)\\ \Delta =1+288\\ \Delta =289\\ \sqrt { 289 } =17\\ \\ \frac { 1\pm 17 }{ 8 } \\ \\ y^{ 1 }=\frac { 9 }{ 4 } \\ y^{ II }=-2

O y duas linhas não serve.


\frac { 2^{ x } }{ 3^{ x } } =\frac { 9 }{ 4 } \\ (\frac { 2 }{ 3 } )^{ x }=\frac { 3^{ 2 } }{ 2^{ 2 } } \\ (\frac { 3 }{ 2 } )^{ -x }=(\frac { 3 }{ 2 } )^{ 2 }\\ \\ -x=2\quad (-1)\\ x=-2